Analisis Perhitungan Harga Pokok Produksi Dengan Metode Harga Pokok Pesanan (Job Order Costing) Pada Amsha Konveksi - Cindy Felini; Rasyidah Mustika; Meri Ulfa Nely (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The business environment in Indonesia is increasingly competitive, encouraging companies to improve performance through effective policies, especially in determining production costs. Accurate cost calculation helps management in planning and controlling production, improving product quality, setting appropriate selling prices, and achieving targeted profits. One suitable method is Job Order Costing. This study aims to determine the cost of production using the Job Order Costing method, prepare order cost cards, and generate order profitability reports at Amsha Konveksi. A qualitative approach is used, with data collected through interviews and observations, including order lists, raw materials, supporting materials, and labor wages. In June 2025, Amsha Konveksi received five types of orders: Qurban T-shirts, jerseys, KKN vests, Jersey T-shirts, and Polo T-shirts, totaling 26 job orders. The profitability report shows a gross profit of Rp14.542.714 (36%) and a net profit of Rp11.043.714 (27%) after administrative and operational expenses. It is recommended that the company maintain proper transaction records and monitor selling prices for each product size. Implementing Job Order Costing with order cost cards will help the company determine profitability more accurately and produce reliable reports.